New combinations in Neotropical Lycopodiaceae - Øllgaard, Benjamin (Phytotaxa, 2012)
This paper proposes new nomenclatural combinations for accepted Neotropical species, according to a new classification with nine Neotropical genera in three subfamilies of the Lycopodiaceae. New combinations for the species occurring in Brazil, are proposed elsewhere (Øllgaard, in press). There is one new combination in Palhinhaea, 119 in Phlegmariurus, and two in Pseudolycopodiella.